2017
DOI: 10.1186/s12905-017-0444-5
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cervical disease among symptomatic women with histopathological sample at Hawassa University referral hospital, Southern Ethiopia

Abstract: BackgroundCervical cancer is one of the most common cancers of women in developing countries. It is also eminent cause of mortality and morbidity in women worldwide. Symptoms usually develop when the cancer has become invasive and invade nearby tissue. This has significant effect on treatment of cases in area where there is limited awareness. The aim of this study is to describe cervical disease among symptomatic women with a histhological sample at Hawassa University referral hospital, southern Ethiopia.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 19 publications
7
10
0
Order By: Relevance
“…of patients encountered in our study were of sexually active age group i.e.30-50 years, most common age group affected being 41-50 years (41.57%). Similar results were seen by PallipadyA et al [6] and Ameya G et al [5] In our study nonsmokers and non-tobacco users accounted for 135 cases (48%) followed closely by tobacco users comprising 47.3% of total cases. Smokers were only 3.94%.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…of patients encountered in our study were of sexually active age group i.e.30-50 years, most common age group affected being 41-50 years (41.57%). Similar results were seen by PallipadyA et al [6] and Ameya G et al [5] In our study nonsmokers and non-tobacco users accounted for 135 cases (48%) followed closely by tobacco users comprising 47.3% of total cases. Smokers were only 3.94%.…”
Section: Discussionsupporting
confidence: 92%
“…This was closely followed by hysterectomy specimens (46.2%). Similar results were seen by Ameya G et al, [5] they also reported biopsy as the most common specimen type (76.2%). Hysterectomies were more common in cases reported malignant in our study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, in Africa it is rather challenged by many factors including limited resources, lack of knowledge about the cervical cancer and unavailability of screening centers (52,53). It was estimated that the overall cervical cancer screening in Ethiopia was 0.8% according to the ICO Information Centre on HPV and Cancer 2017 (54). Similarly, it was reported to be 1% in another study done by Getachew et al (52).…”
Section: Uterine Cervical Cancermentioning
confidence: 99%
“… 8 Cervical cancer ranks as the second most frequent cancer among women in Ethiopia and the leading cause of cancer related deaths. 9 Studies revealed that the age-adjusted incidence rate of cervical cancer in Ethiopia is 35.9 per 100,000 patients, with 7,619 new cases and 6,081 deaths every year. 10 The distribution of the problem across different regions in Ethiopia between 1997–2012 was 32.98%, 30.15%, and 19.72% in Addis Ababa, Oromia, and Amhara, respectively.…”
Section: Introductionmentioning
confidence: 99%